Multi-scale 3D rock-art recording. Issue 2 (2015) - Alexander, Craig; Pinz, Axel; Reinbacher, Christian
Abstract: We present the micro- and mid-scale elements of an integrated multi-scalar solution to the 3D recording of rock-art sites in their landscape contexts. The photogrammetry-based solution integrates 3D models across vastly different scales: individual petroglyph, rock-art panel, site, landscape context. Micro-scale data are acquired with a novel 3D scanner that offers unprecedented radiometric quality at a resolution of 0.1 mm and immediate in-field user feedback while mid-scale data are acquired by unmanned micro-aerial vehicles. At all spatial scales the data are processed in a common Structure-from-Motion environment. Our solution is being tested in Valcamonica in northern Italy. One approximately 400 m 2 panel – Seradina I Rock 12C – is used throughout the paper to illustrate the approach and results. 3D point clouds are provided as digital supplementary material. It is shown that the solution is well-suited to purpose and will be of value to rock-art archaeology more generally.